Correlation Of Visual Perception And Activities Of Daily Living In Acute Hemiparesis Resulting From Cerebro Vascular Accident - D.SURESH; C. ELAMATHI (International Journal of Pharma and Bio Sciences, 2015)
The objective of this study is to correlate visual perception and activities of daily living in acute hemiparesis resulting from cerebrovascular accident. Quantitative Study design was used and was conducted in SRM hospitals at Kancheepuram and Vijaya Health Centre at Chennai. The samples were 36 subjects with either clinically definite, and laboratory supported with average age limit 46.33 years .Outcome measures like MoCA ,Beery-Buktenica Developmental Test of Visual-Motor Integration and Functional Assessment Measures were used in this study. The results indicated that Visual perception has a strong positive correlation with ADL. The visual perceptual deficits influence VMI which is considered to be the pre requisites for ADL. Visual perceptual deficits are most notably present in self care, locomotion and communication in acute Hemiparetic patients. The influence of visual perceptual deficits on ADL is comparatively high in patients with Left Hemiparesis than with the Right Hemiparesis.